The Dynamics of Urban Muslim Families Post-Divorce: The Contribution of Islamic Law in Building Resilience of Indonesian and Malaysian Families - Hamidah, Tutik; Furaida, Asni; Rosdiana, Aprilia Mega; Sulalah, Sulalah; Rahman, Noor Naemah Abdul (Shariah Faculty UIN Maulana Malik Ibrahim Malang, 2024)
Divorce is currently an increasingly comon phenomenon in urban area, including among Muslims in Indonesia and Malaysia. This phenomenon raises legal, social and psychological challenges that affect family resilience after divorce. Family resilience is not confined solely to the upper-middle-class, but also to all individuals striving to persevere in their daily lives after divorce. This research aims to explore the legal behavior of urban Muslims after divorce, with a focus on how individuals in these two countries deal with issues related to economic, socio-cultural and psychological issues. This is field research that uses qualitative methods related to the dynamics of family resilience in urban Muslim communities in Indonesia and Malaysia. The research was conducted using in-depth interviews. The results of this research are that each post-divorce family has a dynamic process in achieving family resilience. Factors that influence family resilience are not only oneself but also social support. This process needs to be strengthened by government support with strategic policies to ensure the fulfillment of post-divorce rights which can speed up the resilience process. Malaysia is more advanced in dealing with post-divorce family resilience with the existence of Bahagian Sokongan Keluarga (BSK). This research is able to contribute to the study of Islamic law and family resilience after divorce. In addition, this research offers strategic insights for the development of more inclusive policies and an Islamic legal perspective to support social justice and family welfare after divorce in both countries.